Esensi Penyelesaian Sengketa Perdata melalui Mediasi Nonlitigasi - Muten Nuna; Ibrahim Ahmad; Agustina Bilondatu; Dince Aisa Kodai; Roy Marthen Moonti (Journal of Judicial Review, 2021)
There are legal issues in the society which resolved through a non-litigation mediation process, especially in civil disputes, where there are several factors that influence people prefer to settle legal issues through non-litigation aspects rather than resolving cases by litigation or through the court. This article aims at explaining how the principles and stages of civil dispute resolution through non-litigation mediation and the essence or value that can be used for the society in dispute. So it can be concluded that this article wants to explain that non-litigation mediation in principle has a consensual as well as collaborative nature, so the result will have win-win solution for each sides, so that the problematic side is cannot be harmed. Then there is a very large value which can be taken, if several problems that arise in society, especially in civil cases which resolved through non-litigation mediation aspects.